Medical thoracoscopy- an experience - Shah, Naveed Nazir; Mehfooz, Nazia; Farooq, Syed Suraya; Dar, Khurshid A.; Shumayl, .; Tariq, . (International Journal of Research in Medical Sciences, 2017)
Background: Medical thoracoscopy is a minimally invasive procedure for diagnosing and treating pleural diseases especially undiagnosed exudative pleural effusion. It is cost effective and safe. The diagnostic yield in undiagnosed pleural effusion is excellent. Methods: This prospective observational study was done in Government Chest Disease hospital of Government Medical College, Srinagar during the period between December 2015 to Dec 2016.Thirty undiagnosed pleural effusion patients after thoracocentesis and who fulfilled inclusion and exclusion criteria’s were included in the study. Medical thoracoscopy using rigid thoracoscope was started for the first time in our hospital and was done in these enrolled patients. Clinical, Thoracoscopic findings and histopathological data of the patients were collected prospectively and analysed. Results: Maximum patients were in the age group of 41-50 years. Most common Thoracoscopic finding was multiple nodules (40%) followed by sago grain infiltration (33.4%). Malignancy was the most common HPE finding of pleural biopsy (46.6%) followed by TB (33.3%). All nodules (13) turned out to be malignant while all sago grain appearance pleura (10) turned out of to be TB. The overall diagnostic yield is 80% as a whole and 96% among patients who had thoracoscopic pleural findings. Conclusions: Medical Thoracoscopy is a safe and easy outpatient procedure and an excellent diagnostic tool for undiagnosed exudative pleural effusion. The diagnostic yield is quite high and complications of procedure are negligible.